Development of acousto-optic spatial light modulator unit for effective control of light beam intensity and diffraction angle in 3D holographic display applications - Kondalkar, Vijay V.; Ryu, Geonhee; Lee, Yongbeom; Lee, Keekeun (Journal of Micromechanics and Microengineering, 2018)
An acousto-optic (AO) based holographic display unit was developed using surface acoustic wave (SAW) with different wavelength to modulate the diffraction angles, intensities, and phases of light. The new configurations were employed to control two beams simultaneously by using a single chirp inter-digital transducer (IDT), and a micro-lens array was integrated at the end of the waveguide layer to focus the diffracted light on to the screen. Two incident light beams were simultaneously modulated by using different refractive grating periods generated from chirp IDT. A diffraction angle of about 5° was obtained by using a SAW with a frequency of 430 MHz. The increase in the SAW input power enhances the diffraction efficiency of the light beam at the exit. The obtained maximum diffraction efficiency is ∼70% at a frequency of 430 MHz. The sloped shape of the waveguide entrance and a tall rounded Ni poles help in coupling the incident light to the waveguide layer. The diffracted beam was collected through the lens, which increased the intensity of light in the viewing plane. COMSOL multi-physics and coupling of mode (COM) modeling were performed to predict the device performance and compared with the experimental results.
Keywords: 3D holographic displays; Device performance; Incident light beams; Intensity of light; Interdigital transducer; Micro-lens arrays; Spatial light modulators; Surface acoustic wave (SAW); acousto-optic (AO); inter-digital transducer (IDT); spatial light modulator (SLM); surface acoustic wave (SAW)